(untitled) (KYAMC Journal, 2017)
Introduction: Sturge-Weber syndrome sometimes referred to as encephalotrigeminal angiomatosis, vascular malformation with capillary venous angiomas involving face, choroid of eye, leptomeninges, is a rare congenital neurological and skin disorder. Case presentation: This is case report of 7 years old mentally disabled boy, with long-standing seizures, with a port-wine nevi on the right side of the face along the distribution of trigeminal nerve. Interictal encephalogram showed bilateral slow activity, pronounced in the right hemisphere, with epileptogenic activity in the right fronto-parietal region. Computerized tomography and magnetic resonance imaging showed intracranial calcifications, abnormally large veins in deep medullary and subependymal periventricular region, atrophy of the right hemisphere of brain and ipsilateral thickening of skull. Conclusion: Professional counselling and support in addition to drug treatment an provide help to patients and their family to overcome their problems and improve the treatment outcome. KYAMC Journal Vol. 4, No.-1, July 2013, Page 366-368